Dampak Posyandu Lansia terhadap Pencegahan Penyakit Kronis pada Usia Lanjut : Studi Kasus Posyandu Lansia di Kelurahan Kutaraya Ogan Komering Ilir - Arie Anggraini; Miftahul Jannah; Wayan Prabowo; Leri Pariski; Lega Purnamasari; Lau'rentia Steveni'a; Melsi Emilia; Desi Priyanti; Na’il Ammamshun Alyahya Putra; Nazjwa Azzahara Karimulah; Puput Meiliani; Rahel Monica; Intan Ali Hanafiyah; M.Riza Nico Albaji; Mardiana Mardiana (JURNAL PENGABDIAN KADER BANGSA, 2026)
The global elderly population continues to grow to 8 billion people at a rate of 1.05% per year, increasing the risk of chronic diseases such as hypertension and diabetes mellitus. This case study evaluates the effectiveness of the Elderly Posyandu in Kutaraya Village, Ogan Komering Ilir, in preventing chronic diseases through a participatory approach for 12 days (February 2-14, 2026), with a focus on educational counseling and cadre training on February 9, 2026. The method includes the preparation, implementation, and evaluation stages using pre-post tests of elderly knowledge (target increase ≥25%), participation absence (≥80%), and observation of cadre behavior. The results show that the majority of elderly do not understand the early detection of chronic diseases. After the activity, they were able to repeat the material and were motivated to regularly attend the Elderly Posyandu. In conclusion, the impact of the elderly Posyandu is very large not only about prevention but also about peace in old age (elderly).